2004
DOI: 10.1002/pi.1626
|View full text |Cite
|
Sign up to set email alerts
|

Frontal copolymerization of 2‐hydroxyethyl methacrylate and ethylene glycol dimethacrylate without porogen: comparison with suspension polymerization

Abstract: Networked, crosslinked poly[(2‐hydroxyethyl methacrylate)‐co‐(ethylene glycol dimethacrylate)] (HEMA‐EGDM) was synthesized by frontal polymerization (FP) using azobisisobutyronitrile as initiator. HEMA‐EGDM copolymers of similar composition were also synthesized by suspension polymerization. The two sets of copolymers were characterized for functional groups (IR), pore volume (mercury intrusion porosimetry), surface area (nitrogen adsorption) and morphology (scanning electron microscopy). FP‐generated polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…[5] The application of FP to synthesize copolymers has been investigated. [6][7][8] Recently, FP was used by Fiori and Mariani for the synthesis of polyurethane, [9] by McFarland and Pojman for the polymerization of 1,6-hexanediol diacrylate with a microencapsulated initiator. [10] In these examples, the rapid reaction rate, observed in propagating fronts, circumvents phase separation which occurs commonly in batch studies.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The application of FP to synthesize copolymers has been investigated. [6][7][8] Recently, FP was used by Fiori and Mariani for the synthesis of polyurethane, [9] by McFarland and Pojman for the polymerization of 1,6-hexanediol diacrylate with a microencapsulated initiator. [10] In these examples, the rapid reaction rate, observed in propagating fronts, circumvents phase separation which occurs commonly in batch studies.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous medium (water) does not remain in the network, but boils off during the polymerization and the purified and dried polymer exhibited permanent pores or holes on loss of porogen. However, the higher FP temperature resulted in smaller pores and hence larger surface area [35]. These particles showed a water regain of 1.6 g/g, corresponding to an overall porosity of 61.53%.…”
mentioning
confidence: 94%
“…Zhai et al, and Koike and Zhang et al have demonstrated the synthesis of gradient refractive index (GRIN) material by isothermal FP [26][27][28]. FP has also been used to cure mortar composition [29], synthesize copolymers [30], hydrogels [31], polymer-dispersed liquid crystals [33], homogeneous polymer blends [34], and crosslinked functional polymers [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pojman and co‐workers later demonstrated the feasibility of FP for a variety of monomers at ambient pressure 18, 19. FP has been used by Washington and Steinbock for the preparation of temperature‐sensitive hydrogels with improved homogeneity,20 and by Pujari et al for the obtainment of porous polymers without porogen 21. Recently, we demonstrated the feasibility of self‐propagating fronts in the synthesis of grafting copolymer hydrogels and the potential for improving the swelling capacity and swelling rate of polymers, which are the desired features of hydrogels 22, 23.…”
Section: Introductionmentioning
confidence: 99%